An Introductory Study of Persian Islamic Literature in 4thand 5thCentury Hijri - Rehman, Naseem ur; Hayat, Shaukat (sourcecoder, 2024)
Persian literature began with the advent of Islam. The earliest works of the Persian language were written in the early centuries of Islam. Along with poetry and literature, there are several historical and religious works in Persian literature. The 4th and 5th centuries Hijri are significant in that most of the Persian religious books were written in these centuries, some of which such as "Kashf al-Mahjub" and "Kemiya-e-Sa’adat" are still popular today. In this paper, a brief introduction to the religious books written in the 4th and 5th centuries of Hijri has been introduced.